An Inverse Problem for the Burgers Equation (Journal of Computational Mathematics, 1993)
In this paper the Generalized Pulse-Spectrum Technique (GPST) is extended to solve an inverse problem for the Burgers equation. We prove that the GPST is equivalent in some sense to the Newton-Kantorovich iteration method. A feasible numerical implementation is presented in the paper and some examples are executed. The numerical results show that this procedure works quite well.